The Role of Quality Statistics in Designing and Evaluating Faith-Based Nutrition Interventions - Hutabarat, Eduward; Sitepu, Yulia Kurnia Sari; Panjaitan, Binur; Enda Dwi Karina; Limmarten Simatupang; Rony Marpaung; Ambarita, Dostri; Melbin Sibagariang (Talenta Publisher, 2025)
Stunting remains a major public health concern in Indonesia, particularly in rural communities where nutritional knowledge and access to health services are limited. This community service program, conducted in October 2024 at HKBP Hutaraja Dolok, aimed to address this issue by integrating quality statistical education with faith-based engagement to empower local communities in monitoring and reducing stunting. The program introduced basic statistical tools—including Z-scores, growth chart interpretation, and prevalence analysis—through interactive workshops targeting caregivers, youth, and church leaders. Religious leaders supported the intervention by embedding health messages within spiritual teachings to promote behavioral change. As a result, participants demonstrated improved understanding of child growth indicators, initiated independent height monitoring, and committed to sustained community involvement. The combination of data literacy and religious motivation proved effective in promoting evidence-based practices, reinforcing the value of statistical empowerment within culturally rooted health programs. This model offers a scalable approach to community-driven stunting interventions in faith-based settings.